2007
DOI: 10.1152/ajpheart.01328.2005
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of NADPH oxidase, antioxidant enzymes, and inflammatory markers in the heart of streptozotocin-induced diabetic rats by N-acetyl-l-cysteine

Abstract: We investigated the effect of N-acetyl-l-cysteine (NAC) on the expression of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, antioxidant enzymes, and inflammatory markers in diabetic rat hearts. Metabolic parameters, free 15-F(2t)-isoprostane level, protein expression of NADPH oxidase, superoxide dismutase (SOD), heme oxygenase (HO-1), interleukin-6 (IL-6), and cyclooxygenase-2 (COX-2) were analyzed in control and streptozotocin-induced diabetic rats treated with or without NAC in drinking water f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
75
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 55 publications
11
75
1
Order By: Relevance
“…Biomarkers for oxidative damage to DNA, lipids, and proteins also supported the concept of increased oxidative stress in diabetes. 21,22) In the present study, there were a significant increase in MDA level and decrease in SOD activity both in heart and kidney tissue, which were consistent with other reports. 23) These results showed that hyperglycemia caused an imbalance between the production of free radicals and the antioxidant defense system in diabetic conditions.…”
Section: Effects Of Losartan On Myocardial Functionssupporting
confidence: 93%
“…Biomarkers for oxidative damage to DNA, lipids, and proteins also supported the concept of increased oxidative stress in diabetes. 21,22) In the present study, there were a significant increase in MDA level and decrease in SOD activity both in heart and kidney tissue, which were consistent with other reports. 23) These results showed that hyperglycemia caused an imbalance between the production of free radicals and the antioxidant defense system in diabetic conditions.…”
Section: Effects Of Losartan On Myocardial Functionssupporting
confidence: 93%
“…Taking this into consideration, NAC treatment aiming at reduced MDA levels represents a promising therapeutic opportunity. But, in spite of many reports reassuring its beneficial effect on oxidative stress (22,(32)(33)(34), our study has failed to reduce MDA concentrations. We do not have a clear understanding about the reason why NAC treatment did not restore normal MDA levels, but we hypothesize that this failure could be related to NAC dose or late onset of NAC treatment.…”
Section: Discussioncontrasting
confidence: 64%
“…Li et al [86] demonstrated that the contractile defect in cardiomyocytes incubated with angiotensin II was abolished by apocynin in association with evidence of reduced activation of Nox2 oxidase. A similar involvement of NADPH-oxidase-derived ROS in cardiomyocyte dysfunction has been suggested in obesity [86], streptozotocin-induced diabetes [87] and [88], aging [89] and gram-negative sepsis [90]. Nox2 is also involved in post-MI contractile dysfunction as discussed in a subsequent section, although this may be secondary to improved remodeling.…”
Section: Contractile Dysfunctionmentioning
confidence: 52%